STUDI KONDISI KUALITAS AIR DI PERAIRAN JUATA KOTA TARAKAN KALIMANTAN TIMUR - Wiharyanto, Dhimas (Jurnal Harpodon Borneo, 2011)
Juata waters is the side of Tarakan Island and it has high biodiversity. The water quality have important rules in this waters as indicator type of waters. Considering that condition a study of water quality condition was very importance. This study was studied from Mei until December 2009. Sampel waters collected at intertidal area with survey method and stratified systematic sampling. In each location divided based on 2 station area every take the sample. From physical parameters condition were founded that transparency about 170 cm until 215 cm, temperature 30 until 31oC and speed of current about 0.31 m/s - 0,61 m/s. Type of tidal in juata waters is Mixed Tide Prevailing Semi Diurnal. Chemical parameters water condition were founded that salinity is about 18.8 until 24.3 promil, pH obout 7.82 - 8.02, Dissolved oxygen (DO) obout 5.17 until 6.50 mg/l, conductor of electicity about 30.1 mS/cm - 38.3 mS/cm, nitrat content about 0,1 mg/l until 0,8 mg/l and fosfat content about 0.38 mg/l until 0.64 mg/l. From this research faounded that nitrat and fosfat content is inversly with plankton abundance. Keywords: Juata waters, water quality, phisycal parameters, chemical parameters.